(untitled) (Confluenţe Bibliologice, 2021)
Most of the serial publications, from the Collection of Rare Documents of USARB Scientific Library, were received as a donation from the Cultural Association Pro Basarabia and Bucovina”, Galati Branch library, secretary Radu Motoc. These documents, carefully collected by collectors, represent bibliophile and historical rarities and constitute a real treasure for the Balti Library. The article addresses the image of Romania through tourism, the importance of tourism objectives in Romania, reflected in the Journal of National Tourism Office.